QTL‐Based Evidence of Population Genetic Divergence in Male Territorial Aggressiveness of the Japanese Freshwater Threespine Stickleback - Haruka Yamazaki; Seiichi Mori; Osamu Kishida; Atsushi J. Nagano; Tomoyuki Kokita (Ecology and Evolution)
ABSTRACT Territorial aggression is widespread across the animal kingdom and is expressed in diverse ecological and social contexts. In addition, there are marked variations in the degree of male reproductive territoriality within and between species. These differences are often attributed to genetic components. However, the evolutionary genetic mechanisms in wild animals are poorly understood. This study explored the genetic basis of divergent male territorial aggressiveness between two Japanese freshwater populations, Gifu (GF) and Tomakomai (TM), in the threespine stickleback, which is a well‐known model system for both behavioral ecology and evolutionary genetics. First, our field survey indicated that the distribution of reproductive territories differed greatly across breeding habitats between the focal populations, and the density of reproductive territories was much greater in the GF population. Second, a one‐on‐one arena aquarium experiment on male–male combat using wild‐caught and common‐garden‐reared males revealed that GF males were genetically more aggressive than TM males. Finally, we performed quantitative trait loci (QTL) analysis using an F2 hybrid cross between the two populations to identify the causal genomic regions contributing to the divergence in male territorial aggressiveness. Our QTL analysis identified a single significant locus in an aggression‐related behavioral component, that is, the number of bites of focal F2 males toward a GF stimulus intruder. Two notable behavior‐related genes, HTR2A and MAO‐A, are found near this locus. These genes have often been suggested to influence of aggressive behavior in animals; therefore, they are regarded as important candidate genes for further functional analyses. Thus, we are the first to provide a QTL‐based genetic basis for population divergence in male territorial aggressiveness in the threespine stickleback.